2021
DOI: 10.1134/s1990747821050032
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Phospholipase A2 Selectivity on POPC/POPG Membranes Using the Interaction Map

Abstract: The regulation of the activity and selectivity of phospholipase A2 (PLA2), which is capable of cleaving fatty acid in the second position (sn-2) of the phospholipid, is carried out through the membrane-binding and catalytic sites of the enzyme. For hydrolytic activity, PLA2 must first bind to the phospholipid membrane, and the binding efficiency depends on the composition of the membrane. The membrane-binding site of PLA2 is formed by several tens of amino acids and its composition differs from enzyme to enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Furthermore, it cannot be excluded that the strong coordination of the negatively charged lipid headgroups by Mg 2+ play an additional role in reducing the PLA2's affinity for the membrane by lowering the membrane negative surface density. Indeed, it was reported that the presence of negatively charged lipids enhances the rate of the reaction, 37 favouring the binding of the enzyme to the membrane, which is the initial step of its action mechanism. Finally, it is important to highlight that, even if our CD experiments did not detect any conformational change of PLA2 imposed by Mg 2+ salts, small local conformational changes ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it cannot be excluded that the strong coordination of the negatively charged lipid headgroups by Mg 2+ play an additional role in reducing the PLA2's affinity for the membrane by lowering the membrane negative surface density. Indeed, it was reported that the presence of negatively charged lipids enhances the rate of the reaction, 37 favouring the binding of the enzyme to the membrane, which is the initial step of its action mechanism. Finally, it is important to highlight that, even if our CD experiments did not detect any conformational change of PLA2 imposed by Mg 2+ salts, small local conformational changes ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The method was used several times to trace sPLA2 binding to the bilayer surface [ 33 , 37 ]. In our previous work, we traced changes in bvPLA2 intrinsic fluorescence upon POPC addition [ 15 , 38 ]. It is important that there is no tryptophan residue in the IBS of bvPLA2 ( Figure 3 , Table S1 ) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMB-PC were prepared. When the ratio of the probe molecules to lipids is 1/4000, no energy transfer is observed between neighboring TMB fluorophores, and the fluorescence anisotropy depends only on the fluorophore mobility [23]. Fluorescence anisotropy of TMB-PC was obtained in a temperature-controlled cell of an F-4000 (Hitachi, Japan) fluorescence spectrometer at 25 • C at λex 475 nm, λem 505 nm.…”
Section: Anisotropymentioning
confidence: 99%